2008
DOI: 10.1149/1.2894189
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bubbles and the Growth Morphology of Ramified Zinc by Electrodeposition

Abstract: Real-time X-ray microscopy was used to study the influence of hydrogen-bubble formation on the morphology of ramified zinc electrodeposit. The experimental results show that when intense hydrogen bubbling occurs at high potential, the morphology of the ramified zinc deposit changes from dense-branching to fern-shaped dendrite. The fern-shaped dendrite results in part from the constricted growth due to hydrogen bubbles but also from the highly concentrated electric field. The fern-shaped dendrite morphology was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 40 publications
1
40
0
2
Order By: Relevance
“…This fact was noted earlier [19,20] but researchers began to put special focus on it in later works [4][5][6][7][8][9][10][11]21]. In most studies [4][5][6][7][8][9][10] the current efficiency of hydrogen was determined by the volume of the gas evolved and taken into account in the form of a constant average value.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…This fact was noted earlier [19,20] but researchers began to put special focus on it in later works [4][5][6][7][8][9][10][11]21]. In most studies [4][5][6][7][8][9][10] the current efficiency of hydrogen was determined by the volume of the gas evolved and taken into account in the form of a constant average value.…”
Section: Introductionmentioning
confidence: 94%
“…There are many works dedicated to the influence of overpotential, electrolysis regime, concentration of the discharging ions and supporting electrolyte on the morphology of loose deposits [4][5][6][7][8][9][10][11]. The model description of the electrocrystallisation of dendritic deposits was proposed by different authors for both potentiostatic [2,3,12,13] and galvanostatic electrolysis conditions [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsu et al demonstrated that hydrogen bubbles directly affect the growth morphology and can make it possible to control the dendritic growth. 56 On analyzing the current variation during CA ( Figure 7A), it was interesting to see that In showed the highest current densities among the four unary systems. Open circuit potentials (OCP) showed most negative values in In(III) electrolyte ( Figure 7D).…”
Section: Resultsmentioning
confidence: 99%
“…Among few operando methods to analyze the distribution of the zinc species, 5,6 X-ray fluorescence (XRF) imaging using a bright synchrotron X-ray source has advantages of elemental labeling, wide observation view and reasonably high spatial-and timeresolutions. 7 Especially, the XRF imaging in reflection geometry allows to capture the distribution of species of interest in a wide area of an electrochemical cell with rapidity, in contrast to the commonly used analytical methods in transmission geometry that is suffered from signal absorption in the electrolyte.…”
Section: Introductionmentioning
confidence: 99%